Pendidikan Politik Bagi Pemilih Pemula Guna Meningkatkan Peran Pemuda dalam Demokrasi - Fransin Kontu; Umiyati Haris; Hesty Tambajong (Universitas Muhammadiyah Manado, 2023)
The democratic system in Indonesia requires active participation from the community, especially the youth. In the electoral system, these young people are referred to as Beginner Voters, who have been able to exercise their voting rights for the first time. This service aims to increase the youth community's understanding of the importance of being actively involved in the electoral system implemented in their neighbourhood. Through political education, understanding of the democratic system and the role of youth as novice voters is part of what this service aims to achieve. This community service was carried out in Yanggandur Village, Sota District, Merauke Regency. The method used in this service is the delivery of material about the Political System in Indonesia; Election System and the Role of Youth in a democratic system, which is delivered through lecture and presentation methods. The result of the socialisation in this service is a real positive impact on increasing understanding of the importance of active participation of youth in the political system, especially the electoral system. So that it will increase the active participation of the Yanggandur community in the upcoming elections.